Use of educational technology as a methodological strategy in the teaching and learning process of human anatomy - Miranda Amador, Samuel Murilo; Rodrigues dos Santos, Taísa; Cunha Brito, Ana Júlia; Dias, George Alberto da Silva; Araújo Cardoso Dias, Biatriz (Pará Research Medical Journal, 2023)
Among the possibilities of active methodologies that can be used in human anatomy classes, the portfolio has been gaining prominence, as it is an instrument that brings together several manual skills. When developing their own instrument, the student builds his knowledge, freeing himself from the condition of mere receiver and becomes part of his learning process. Purpose: To report the process of building and using the portfolio as an educational technology in the human anatomy discipline. Methods: This is a methodological study of the production of educational technology, carried out at the Centro Universitário Metropolitano da Amazônia with students from the 1st and 2nd semester. Students should previously bring drawings related to human anatomy subjects and during classes they could improve them and thus create their own portfolio. The preparation of the material went through the following phases: situational diagnosis, literature review and portfolio construction. Results: It was possible to observe that the use of the portfolio was a good strategy for the teaching and learning process of human anatomy. Because it can strengthen the relationship between teacher and student, in addition to developing a sense of critical evaluation of their production and with that, increase the search for information and improve learning. Conclusions: The use of the portfolio fostered the construction of an educational technology where the student was the protagonist of his own learning. Thus, it was observed that the result of this strategy was satisfactory during the learning process of the contents covered in the discipline of human anatomy.